Advancing a Stem Cell Therapy for Age-Related Macular Degeneration - O'Neill, Helen C.; Limnios, Ioannis J.; Barnett, Nigel L. (Current Stem Cell Research & Therapy, 2020)
The retinal pigment epithelium (RPE) is a multifunctional monolayer located at the back of the eye required for the survival and function of the light-sensing photoreceptors. In Age-related Macular Degeneration (AMD), the loss of RPE cells leads to photoreceptor death and permanent blindness. RPE cell transplantation aims to halt or reverse vision loss by preventing the death of photoreceptor cells and is considered one of the most viable applications of stem cell therapy in the field of regenerative medicine. Proof-of-concept of RPE cell transplantation for treating retinal degenerative disease, such as AMD, has long been established in animal models and humans using primary RPE cells, while recent research has focused on the transplantation of RPE cells derived from human pluripotent stem cells (hPSC). Early results from clinical trials indicate that transplantation of hPSC-derived RPE cells is safe and can improve vision in AMD patients. Current hPSC-RPE cell production protocols used in clinical trials are nevertheless inefficient. Treatment of large numbers of AMD patients using stem cellderived products may be dependent on the ability to generate functional cells from multiple hPSC lines using robust and clinically-compliant methods. Transplantation outcomes may be improved by delivering RPE cells on a thin porous membrane for better integration into the retina, and by manipulation of the outcome through control of immune rejection and inflammatory responses.
Keywords: Pluripotent stem cells